(untitled) (Research, Society and Development, 2023)
Nosocomial infections are infections acquired in a hospital environment, strongly associated with patient severity processes. Thus, inadequate or non-existent cleaning of fomites strongly corroborates this process. The present study aimed to identify the bacteria Escherichia coli and Klebsiella pneumoniae in cell phones and stethoscopes belonging to the multiprofessional team or to the hospital itself, to verify the frequency of cleaning of these, as well as to identify possible resistance of the bacteria to antibiotics, in order to understand the impact of these on nosocomial infections in the hospital analyzed. The samples were collected with sterile swabs and analyzed in the laboratory for biochemical identification and verification of antibiotic resistance using the Kirby Bauer technique. Objective questionnaires were also applied to the participants. Fifty samples were collected, in which 93.10% (27/29) of cell phones and 95.23% (20/21) of stethoscopes indicated contamination. Considering only stethoscope samples, their colonization by Klebisiella pneumoniae has an index of almost 5%, while analyzing cell phone samples we obtained 3.5% contamination by E.coli. The E.coli bacterium isolated in this study did not show resistance to any of the antibiotics, while the Klebsiella sample was resistant to all the antibiotics tested. Regarding the questionnaires, 34.4% of the participants said they clean their mobile phones daily, while only 3 participants (14%) said they clean their stethoscopes after each patient. Although the rates of Escherichia coli and Klebsiella pneumoniae in the cell phones and stethoscopes studied were not high, this study addresses an extremely relevant topic and collaborates with the development of possible interventions to reduce nosocomial infections.